Phenotypic and Genetic Characterization of a Maize Association Mapping Panel Developed for the Identification of New Sources of Resistance to Aspergillus flavus and Aflatoxin Accumulation. Issue 6 (1st November 2013) - Warburton, Marilyn L.; Williams, W. Paul; Windham, Gary L.; Murray, Seth C.; Xu, Wenwei; Hawkins, Leigh K.; Duran, Jorge Franco
ABSTRACT: Maize ( Zea mays L.) susceptibility to ear rot by Aspergillus flavus (Link:Fr) and aflatoxin accumulation causes global economic and human health damage. Host plant resistance is an ideal solution, but commercial varieties lack sufficient resistance to solve the problem. Due to general lack of resistant maize germplasm, no currently available association mapping panels are expected to contain significant variation for the trait. A new association mapping panel containing the majority of aflatoxin accumulation resistant maize lines at the time of compilation is presented here along with genetic and phenotypic characterization data. Phenotypic data from testcrossed lines include aflatoxin levels, days to silking, and corn earworm [ Helicoverpa zea (Boddie)] damage measured in seven environments and fungal biomass of kernels measured in three. In addition to identifying previously reported aflatoxin resistant lines, new resistant lines were discovered, which may be used for breeding improved germplasm. The Mexican landrace Tuxpeño is the progenitor or one main contributor for most of the resistant lines and likely the source of resistance, but a few other sources may allow additional novel resistance to be pyramided into future breeding lines. Genetic characterization of kinship, genetic diversity, and substructure analysis presented here will allow this resource to be used for association mapping of aflatoxin and identification of factors responsible for this challenging quantitative trait.